Increased agitation reliability for slurry suspension in mineral processing. (15th August 2021) - Wu, J.; Nguyen, B.; Graham, L.; Hurley, M.; Harris, D.; Short, G.; Kieruj, J.; Connor, Tom
Highlights: Swirl Flow minimises tank maintenance by improving the reliability in agitation and mixing. Swirl flow could provide more energy efficient suspension compared with draft tubes or multiple impeller designs. Swirl Flow is capable of suspending solids at very high concentration. A more uniform velocity is generated with Swirl Flow to reduce formation of scale lumps. Abstract: Regular maintenance shutdowns are required for mineral processing tanks to clean sedimentation and scale. The labour cost and loss of production during maintenance negatively impact on the economics of the operation. Swirl Flow (SF) technology was developed to improve the reliability of agitation and to maximise tank online time between maintenance intervals. This technology simplifies the engineering in agitator mechanical design with reduced shaft length and removal of baffles. Tests showed that swirling flow could provide more energy efficient suspension compared with draft tubes or multiple impeller designs. It is demonstrated that SF is capable of suspending solids at very high concentration, which is impractical with a conventional agitator. A more uniform velocity over the tank wall surface is generated under SF, free of stagnant zones in the upper corner of the tank and other areas commonly encountered in conventional agitator designs. This feature reduces the formation of large lumpy scale that could form in the stagnant zones. Compared with a conventional agitator designs, SF provides mixing homogeneity with slightly longer mixing time.